The Effectiveness of Using the Mind Mapping Method in Growing Motivation for Learning Islamic Cultural History - Muddin, Imam (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
In developing the self-potential of students, educators are expected to have methods or methods, educators must be creative in choosing methods that are appropriate to the learning material. Based on the observations of researchers in the field, it shows that there are problems faced by students of class VI C MIN 15 Magetan in studying the History of Islamic Culture. They are less motivated, even bored during the learning process. Starting from these problems the researchers tried to use a new learning method in conveying the material of Islamic Cultural History, namely the Mind Mapping learning method. To obtain complete data, this study uses a qualitative approach to retrieve, analyze, and process data and information created to answer problems. The results show that the application of the mind mapping method can increase student learning motivation, increase student activity and increase student creativity